Establishment of a novel double-monoclonal antibody sandwich enzyme-linked immunosorbent assay (ELISA): tool for human B7-H4 detection in autoimmune diseases. (6th June 2021) - Ding, Sisi; Zhou, Hengxin; Gu, Yanzheng; Shen, Yu; Zhang, Li; Zhao, Huayang; Wu, Jian; Zhang, Xueguang; Chang, Xin; Liu, Cuiping
Summary: B7-H4, one of the immunoregulatory proteins, plays an inhibitory role by inhibiting T cell proliferation and cytokine production. Nevertheless, the significance of soluble B7-H4 (sB7-H4) in autoimmune diseases is unclear. In our study, we developed two novel mouse anti-human B7-H4 monoclonal antibodies (mAbs) (clones 8D4 and 7E1) with utilities for flow cytometry, immunoblotting and immunofluorescence. We characterized 7E1 as a functional antibody with antagonistic activity, which could promote T cell proliferation and regulate cytokine production. Furthermore, based on the different epitope specificities, we established a novel enzyme-linked immunosorbent assay (ELISA) which could detect sB7-H4 sensitively and specifically. Using this ELISA kit, sB7-H4 was observed in a high proportion of autoimmune diseases patients. We found that the levels of sB7-H4 were significantly higher in patients with systemic lupus erythematosus (SLE), type I diabetes (T1D) and Graves' disease (GD). Together, sB7-H4 in human serum is regarded not only as a regulator of T cell activation but may also be a diagnostic marker of autoimmune diseases. Graphical Abstract: